COVID-19 Recombinant mRNA Vaccines and Serious Ocular Inflammatory Side Effects: Real or Coincidence? - Arash Maleki; Sydney Look-Why; Ambika Manhapra; C. Stephen Foster (Journal of Ophthalmic & Vision Research)
Abstract Purpose: To report two cases; bilateral arteritic anterior ischemic optic neuropathy (AAION) and bilateral acute zonal occult outer retinopathy (AZOOR) after COVID-19 mRNA vaccination. Case Reports: The first patient was a 79-year-old female was presented to us 35 days after a sudden bilateral loss of vision, which occurred two days after receiving the second recombinant mRNA vaccine (Pfizer) injection. Temporal artery biopsy was compatible with AAION. At presentation, the best-corrected visual acuity was 20/1250 and 20/40 in the right and left eyes on the Snellen acuity chart, respectively. There was 3+ afferent pupillary defect in the right eye. The anterior segment and posterior segment exams were normal except for pallor of the optic nerve head in both eyes. Intraocular pressure was normal in both eyes. She was diagnosed with bilateral AAION and Subcutaneous tocilizumab 162 mg weekly was recommended with monitoring her ESR, CRP, and IL-6. The second patient was a 33-year-old healthy female who was referred to us for a progressive nasal field defect in her left eye, and for flashes in both eyes. Her symptoms started 10 days after receiving the second recombinant mRNA vaccine (Moderna) injection. Complete bloodwork performed by a uveitis specialist demonstrated high ESR (25) and CRP (19) levels. As a result, she was diagnosed with unilateral AZOOR in her left eye and was subsequently treated with an intravitreal dexamethasone implant in the same eye. At presentation, vision was20/20 in both eyes. The anterior segment and posterior segment exams were completely normal except for the presence of abnormal white reflex in the temporal macula of her left eye. We diagnosed her with bilateral AZOOR. Since she was nursing, intravitreal dexamethasone implant was recommended for the right eye. Conclusion: There may be a correlation between ocular inflammatory diseases with autoimmune mechanism and the mRNA COVID-19 vaccination.